Earthworm Bioindication of Forest Land Use Pattern - Behera, B.; Giri, S.; Dash, Nabin C.; Sahu, J.; Senapati, B. K. (Indian Forester, 1999)
The present work is an example to substantiate the value of earthworm community for bioindication of land use pattern in comparison to the native forest. Earthworm biodiversity indices, population dynamics, biomass values have been used through Principal Component Analysis (PCA) and the result has been compared with soil chemical parameters. Eucalyptus plantation has revealed the worst situation of land use pattern in comparison to degraded forest and shifting cultivation.